Rozwiązane

Usuń nawiasy i zredukuj wyrazy podobne.
3x – ( -9x -11) + 6=
(4a + 5b -1) – (2 + 6b – a)=
-( - ( -9x)) + (- (- 6)) + ( -1 -3x)=
-4x2 + ( x – x2 ) – ( - 5x + 5x2)=
( a + b + 4) + (- 6 – a + b ) –b =
(x – ( -x – 9) + ( x + 7 ) – 3x) + 5 + 8x=
11a + 5 – ( -6 -2a) -7a=
-( - 2x-( -2x- ( 3x +6) -5) +8x)=
(34a + 7b -6) – (-13 +65a – 38b) =
Usuń nawiasy, zredukuj wyrazy podobne i oblicz wartość dla x=2, y= -6.
-x – (- 5x – 6) + 4 +7x=
13y2 + ( 2x2 – y2) + 11x2=
( x + y) – ( x+ y) + ( x -y)=
- x + (- y – y2) + ( x – y ) –y2=
8x + 5 + ( x –(x – (x-1)))=
(x2 + y2 -6) + ( 3 – 6x2) – ( 5 – 6y2)=
12x – x + x – 5x+ ( 4x – 7) -12x=